2000
DOI: 10.2307/3318580
|View full text |Cite
|
Sign up to set email alerts
|

Large Deviations for Stochastic Volterra Equations

Abstract: This paper is devoted to prove a large-deviation principle for solutions to multidimensional stochastic Volterra equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Using the Skorohod integral, Pardoux and Protter [47] also investigated stochastic Volterra equations with anticipating coefficients. The study of stochastic Volterra equations with singular kernels can be found in [14,16,65,36,44], etc. Recently, the present author [68] studied the approximation of Euler's type and the LDP of Freidlin-Wentzell's type for stochastic Volterra equations with singular kernels.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Skorohod integral, Pardoux and Protter [47] also investigated stochastic Volterra equations with anticipating coefficients. The study of stochastic Volterra equations with singular kernels can be found in [14,16,65,36,44], etc. Recently, the present author [68] studied the approximation of Euler's type and the LDP of Freidlin-Wentzell's type for stochastic Volterra equations with singular kernels.…”
Section: Introductionmentioning
confidence: 99%
“…Then X ε · (·, ω) ∈ C for almost all ω ∈ Ω by Theorem 1.1. Another main result in this paper is to prove the following Freidlin-Wentzell's large deviation estimate that extends Nualart-Rovira's result [14].…”
Section: Introduction and Main Resultsmentioning
confidence: 91%
“…(1) can be proved directly by successive approximation and Gronwall's inequality. A Freidlin-Wentzell's type large deviation principle in continuous functions space for stochastic Volterra equation has been established by Nualart and Rovira in [14]. This result was later improved to the BesovOrlicz space by Lakhel in [11].…”
Section: Introduction and Main Resultsmentioning
confidence: 93%
“…The distance on C 0 induced by the supremum norm will be denoted by d. Denote by H the Cameron -Martin space associated with Brownian motion, i.e. the set of the absolutely continuous functions h [ C 0 such that khk Nualart and Rovira [10] have proved that the solution of (1.1) satisfies the large deviation principle (LDP). In their paper it is supposed that s 1 ¼ s and b 1 ¼ b; the same proofs, however, still work in our case and we have the following: Theorem 1.…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%